Psychological distress among the B40 population in Selangor / Dini Hazwani Zailani, Syamsul Anwar Sultan Ibrahim and Rosilah Wahab - Zailani, Dini Hazwani; Sultan Ibrahim, Syamsul Anwar; Wahab, Rosilah (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
Mental illness affects one-fourth of people worldwide, making it one of the significant contributors to the disease burden in today's fast urbanizing society. Psychological distress is always accompanying mental health; according to various researchers, depression and anxiety are indicators of a condition of emotional suffering. The severity of the symptoms and their influence on the person's everyday life determine the level of distress. This study aimed to determine the prevalence of psychological distress among the B40 adult population in Selangor and to identify any differences between psychological distress and demographic characteristics. A cross-sectional study was conducted online with 181 participants from the B40 group in Selangor. Findings revealed that more than half of the respondents for this study have a high risk of developing mental health problems where demographic data such as age, marital status, occupation, ethnicity and educational status can influence developing psychological distress. Therefore, it is essential to prevent or reduce the risk of psychological distress among this group by recommending them to seek treatment with the related parties.